Associations and Heritability of Auditory Encoding, Gray Matter, and Attention in Schizophrenia. (7th August 2018) - Chen, Yu-Han; Howell, Breannan; Edgar, J Christopher; Huang, Mingxiong; Kochunov, Peter; Hunter, Michael A; Wootton, Cassandra; Lu, Brett Y; Bustillo, Juan; Sadek, Joseph R; Miller, Gregory A; Cañive, José M
Abstract: Background: Auditory encoding abnormalities, gray-matter loss, and cognitive deficits are all candidate schizophrenia (SZ) endophenotypes. This study evaluated associations between and heritability of auditory network attributes (function and structure) and attention in healthy controls (HC), SZ patients, and unaffected relatives (UR). Methods: Whole-brain maps of M100 auditory activity from magnetoencephalography recordings, cortical thickness (CT), and a measure of attention were obtained from 70 HC, 69 SZ patients, and 35 UR. Heritability estimates ( h 2 r ) were obtained for M100, CT at each group-difference region, and the attention measure. Results: SZ patients had weaker bilateral superior temporal gyrus (STG) M100 responses than HC and a weaker right frontal M100 response than UR. Abnormally large M100 responses in left superior frontal gyrus were observed in UR and SZ patients. SZ patients showed smaller CT in bilateral STG and right frontal regions. Interrelatedness between 3 putative SZ endophenotypes was demonstrated, although in the left STG the M100 and CT function−structure associations observed in HC and UR were absent in SZ patients. Heritability analyses also showed that right frontal M100 and bilateral STG CT measures are significantly heritable. Conclusions: Present findings indicated that the 3 SZ endophenotypes examined are not isolated markers of pathology but instead are connected. The pattern of auditory encoding group differences and the pattern of brain function−structure associations differ as a function of brain region, indicating the need for regional specificity when studying these endophenotypes, and with the presence of left STG function−structure associations in HC and UR but not in SZ perhaps reflecting disease-associated damage to gray matter that disrupts function−structure relationships in SZ.